PENGARUH PENGEMBALIAN KREDIT NASABAH TERHADAP KINERJA KEUANGAN PADA KOPERASI SERBA USAHA MODERN KOTA MEDAN TAHUN 2016-2020 - HILMAN LUBIS (JURNAL ILMIAH MAKSITEK, 2020)
According to Law no. 25 of 1992 paragraph 1, Financial Statements are part of the accountability of the management to its members in the annual meeting (RAT), financial statements usually include statements of financial position, reports of residual results, and cash flow reports which are presented in a comparative manner and must be signed by all members. cooperative management.Financial performance is an assessment of the company's financial statements regarding the company's financial position and changes in the company's financial position. Assessment of financial performance based on financial data and information is a benchmark that is often used in obtaining information about a business entity's financial position.Credit repayments made by customers affect the level of smoothness of the loan according to age, customer education level and the presence of collateral. The variables of age and education have a negative coefficient, but the collateral variable has a positive coefficient. Thus, the increasing age and the higher the level of education of customers, the likelihood of arrears will be high. Conversely, the existence of collateral will reduce the possibility of arrears on credit repayments. Modern Multipurpose Cooperative (KSU) is one of hundreds of cooperatives that were born, grown and developed in the city of Medan. Initially, in 2011 this cooperative only had 40 members, but with hard work and still upholding honesty, Modern KSU continues to grow in terms of the number of members and the number of capital